Pallada‐ and platinacycle complexes of phosphorus ylides; synthesis, X‐ray characterization, theoretical and electrochemical studies and application of Pd(II) complexes as catalyst in Suzuki‐Miyaura coupling reaction. (12th May 2017) - Sabounchei, Seyyed Javad; Sedghi, Asieh; Hashemi, Ali; Hosseinzadeh, Marjan; Bayat, Mehdi; Gable, Robert W.
Abstract : The new unsymmetrical phosphonium salts [Ph2 PCH2 PPh2 CH2 C(O)C6 H4 R]Br (R= m ‐Br (S 1 ) and p ‐CN (S 2 )) were synthesized in the reaction of 1, 1‐bis(diphenylphosphino)methane (dppm) and BrCH2 C(O)C6 H4 R (R= m ‐Br and p ‐CN) ketones, respectively. Further treatment with NEt3 gave the α‐keto stabilized phosphorus ylides Ph2 PCH2 PPh2 C(H)C(O)C6 H4 R (R= m ‐Br (Y 1 ) and p ‐CN (Y 2 )). These ligands were reacted with [MCl2 (cod)] (M= Pd and Pt; cod= 1, 5‐cyclooctadiene) to give the pallada‐ and platinacycle complexes [MCl2 (Ph2 PCH2 PPh2 C(H)C(O)C6 H4 R)] (M= Pd, R= m ‐Br (3 ); R= p ‐CN (4 ) and M= Pt, R= m ‐Br (5 ); R= p ‐CN (6 )). Cyclic voltammetry, elemental analysis, IR and NMR ( 1 H, 13 C and 31 P) spectroscopic methods were used for characterization of the obtained compounds. Further, the structure of complexes3 and4 were characterized crystallographically. Palladacycles3 and4 were proved to be excellent catalysts for the Suzuki‐Miyaura coupling reactions of various aryl chlorides and arylboronic acids in mixed DMF/H2 O media. Also, the bonding situations between two interacted fragments [PtCl2 ] andY 1 andY 2 ligands in platinacycles5 and6 were investigated based on DFT method by using NBO, EDA and ETS‐NOCV analysis. Abstract : We report the synthesis and characterization of new pallada‐ and platinacycle complexes [MCl2 (Ph2 PCH2 PPh2 C(H)C(O)C6 H4 R)] (M= Pd and Pt, R = m ‐Br and p ‐CN) and application of Pd(II) complexes as catalyst in Suzuki‐Miyaura coupling reaction.